2020
DOI: 10.3390/ma13081827
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Recycled Polypropylene Fibers as an Addition to Concrete Fabrication Based on Portland Cement

Abstract: High-performance concrete has low tensile strength and brittle failure. In order to improve these properties of unreinforced concrete, the effects of adding recycled polypropylene fibers on the mechanical properties of concrete were investigated. The polypropylene fibers used were made from recycled plastic packaging for environmental reasons (long degradation time). The compressive, flexural and split tensile strengths after 1, 7, 14 and 28 days were tested. Moreover, the initial and final binding times were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 67 publications
7
46
2
2
Order By: Relevance
“…The whole mixing time lasts about 6 min. The mixing process in the present study is similar to that by Małek et al [29]. When the fiber volume fraction attains 2%, it is found that some difficulty is encountered more or less during the mixing process.…”
Section: Productionsupporting
confidence: 87%
See 3 more Smart Citations
“…The whole mixing time lasts about 6 min. The mixing process in the present study is similar to that by Małek et al [29]. When the fiber volume fraction attains 2%, it is found that some difficulty is encountered more or less during the mixing process.…”
Section: Productionsupporting
confidence: 87%
“…The CAC with no fiber reinforcement is adopted as the control concrete. Moreover, Małek et al [29] pointed out that the workability of fresh concrete becomes weaker as the fiber content increases. Because the fiber content varies in a relatively wide range in the present study, different superplasticizer additions are needed in order to ensure the slump of all the fresh concrete almost invariable.…”
Section: Proportionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there is a need to look for materials as a replacement for cement or aggregate. Recycled materials are used to limited energy consumption by the concrete industry and the production of concrete as an environmentally friendly material [ 7 , 8 , 9 , 10 ]. The use of fly ash as a replacement for cement was studied by many researchers [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%